Measles Outbreak in Sverdlovsk Region - S. V. Skryabina; S. A. Kovyazina; S. V. Kuzmin; A. I. Yurovskikh; O. V. Tsvirkun; A. G. Gerasimova; N. T. Tikhonova; L. N. Malyamova; S. S. Smirnova; A. N. Kharitonov; E. A. Rybinskova (Эпидемиология и вакцинопрофилактика, 2018)
Objective. In the Russian Federation on the background of the sporadic incidence of measles, the trend is not highly uniform distribution of morbidity on territories of the country with  the formation of local outbreaks, including the result of nosocomial  infection. Find out the causes of the outbreak, for example the  territory, for 15 years keeping and epidemic well-being in relation to  measles, high vaccination coverage in children and adults, to assess  the capacity of health care organizations and epidemiology to  prevent the spread of measles and the elimination of flash was the goal of this research.Material and methods. A retrospective epidemiological analysis was held: the incidence of measles for the period 2001–2016 in the  Sverdlovskiy region ; 76 «Cards epidemiological case investigation  suspected measles», was from October to December 2016; the  analysis of the extraordinary and final reports of the measles  outbreak, reports on the activities carried out in the outbreak  of  measles. Laboratory verification of cases suspected were examined  the ELISA method in the Perm regional centre, on the basis of  detection of specific IgM and/or IgG increase. Molecular genetic  research of 15 clinical specimens were performed at the Scientific- methodical centre on supervision of measles and rubella  (Gabrichevsky Research Institute by Epidemiology & Microbiology»,  Moscow).Results. During the period c from 40 to 51 week of 2016 measles ill 76 people, mostly (66 persons) residents of the city of  Yekaterinburg. Prevailed among the infected children was 67% (51  persons), usually not vaccinated against this infection – 90% (46) of  children had a measles vaccination. All cases were laboratory  confirmed. Expected sources or place of infection was established in  90.8% of cases. Among cases and 72.4% (55 persons) amounted to  unvaccinated against measles, 11.8 per cent(9 people) were vaccinated once, of 15.8% (12) had a two-fold vaccination. In  8 hospitals was 8 foci of measles, 6 of which had spread. Among the  cases of measles identified in health facilities, 35 children and 19  adults, including 5 health workers and 3 medical students. The  formation of foci of nosocomial infection contributed to missed cases  of measles, late diagnosis, significantly reduce the effectiveness of  anti-epidemic measures. The results of molecular genetic studies of  15 clinical samples of patients selected at 42–44, and 47–49 weeks  possible to establish the circulating strains of measles virus genotype D8. Epidemiological investigations and the common genetic variant  circulating genotypes, selected at different stages of measles spread  from different foci made it possible to combine all cases in one  outbreak. Analysis of clinical manifestations of measles have testified to the fact that measles is proceeded typically in 92.2% of cases.  Eleven drifts infection in educational institutions of Ekaterinburg was not accompanied by the secondary spread, indicating good collective immunity.Conclusion. Thus, a retrospective epidemiological analysis of outbreaks of measles showed that in conditions of sporadic measles in doctors reduced vigilance against measles. Late diagnosis of measles and as a consequence of its failure to carry out anti- epidemic measures led to the spread of infection, as well as skid  measles in other medicine organization, which consisted of  nosocomial foci. The present outbreak showed that measles requires  constant attention, especially during her long absence in the region.  It is only possible to prevent sustained secondary transmission if measles vaccination coverage is high for the entire population.